Predicting and Preventing Postoperative Outcomes - Lee, Sung Gon; Russ, Andrew (Clinics in Colon and Rectal Surgery, 2019)
Complications after colorectal surgery are common. Given the frequency of postoperative complications and their implications on quality of life, it is important to know how to predict and prevent the complications that we encounter. This article aims to provide ways to predict and prevent postoperative complications in colorectal surgery. Here, we review the predictive models, American College of Surgeons National Surgery Quality Improvement Program risk calculator and Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity on their practicality and usefulness. Additionally, this review summarizes nonmodifiable and modifiable risk factors in colorectal surgery, which are important for surgeons to understand to minimize and attempt to avoid postoperative complications as well as providing ways to optimize patients preoperatively. Thus, this review will provide information to surgeons to predict and prevent postoperative complications, how to optimize patients preoperatively and ultimately to help reduce their occurrence.
Keywords: postoperative complication; preoperative risk factors; modifiable risk factors; colorectal surgery